The Contribution of Confraternities to the Urban Soundscape of Barcelona in the Early Modern Period - Knighton, Tess (Confraternitas)

(untitled) (Iter Press, 2020)
Sound was important to urban devotional and guild confraternities: sounds of various kinds, including organized and semi-improvised musics, served as acoustic signals that heralded their presence and communicated their identity; and different combinations of sounds characterized their devotional activities and ceremonies. Whether based at the cathedral or a collegiate, parish or conventual church, confraternities developed a sonic identity that drew on shared elements—bells, town criers, the hiring of wind-bands and other musicians such as trumpets and drums, as well as players of stringed instruments, the organ, chant and polyphonic singing, songs and dances—that were combined in various ways according to the devotional needs and economic resources of the confraternity in question, and to the nature of the event in which they were participating. More sound was generally regarded as more prestigious, but this depended on the fluctuating economic situation of individual confraternities. The smaller brotherhoods often struggled to meet the expense of hiring musicians for the annual feast days of their patron saints. Given the proliferation of confraternities in a city such as Barcelona, the density of their devotional activity—in addition to their customary participation in general urban processions, such as those of Holy Week, Corpus Christi, and other major feasts—meant that their contribution to the urban soundscape was considerable: indeed, it is impossible to recover any real sense of it without taking into account their musical patronage and sonic contribution.